Achieving a sustainable global energy system identifying possibilities using long-term energy scenarios - Schrattenholzer, Leo.; Strubegger, Manfred; Totschnig, Gerhard; Zhu, Bing.; International Institute for Applied Systems Analysis; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar Pub., 2004)
Sustainable development and global climate change have figured prominently in scientific analysis and international policymaking since the early 1990s. This book formulates technology strategies that will lead to environmentally sustainable energy systems, based on an analysis of global climate change issues using the concept of sustainable development. The authors focus on environmentally compatible, long-term technology developments within the global energy system, while also considering aspects of economic and social sustainability.
1. Sustainable development and climate change -- 2. Methodology -- 3. Energy-economy-environment scenarios at IIASA-ECS -- 4. Technology clusters -- 5. A sustainable-development scenario in detail -- 6. Summary and policy implications.
"In association with the International Institute for Applied Systems Analysis (IIASA)"--T.p.
Includes bibliographical references and index.
Keywords: Energy policy; Energy development; Energy conservation; Sustainable development; Electronic books